2014
DOI: 10.1155/2014/864512
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Fibroma of Tongue: Understanding the Nature of an Unusual Histopathological Entity

Abstract: Giant cell fibroma (GCF) is a rare case with unique histopathology. It belongs to the broad category of fibrous hyperplastic lesions of the oral cavity. It is often mistaken with fibroma and papilloma due to its clinical resemblance. Only its peculiar histopathological features help us to distinguish it from them. The origin of the giant cell is still controversial. Data available is very sparse to predict the exact behavior. Hence, we report a case of GCF of tongue in a 19-year-old male. Special emphasis is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…16 A possible viral origin of the tumor has also been postulated. 9 The origin of giant multinucleated cells is a matter of discussion. Souza et al 17 found…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 A possible viral origin of the tumor has also been postulated. 9 The origin of giant multinucleated cells is a matter of discussion. Souza et al 17 found…”
Section: Discussionmentioning
confidence: 99%
“…7 Histological examination of GCFs often reveals a hyperplastic stratified squamous epithelium and stellate-shaped, mononuclear, and multinucleated giant cells loosely arranged in vascular connective tissue. 8,10,11 Sonalika et al 9 reported that although the fibroblastic origin of these giant cells is clear, the reason as to why these giant cells are formed still remains uncertain. The giant cells are usually seen numerous in the connective tissue immediately adjacent to the epithelium, have welldefined cell borders, and show dendritic processes.…”
Section: 5005/jp-journals-10024-2160mentioning
confidence: 99%
See 1 more Smart Citation
“…GCF is an unusual fibrous mucosal mass with several unique features separating it from other oral fibrous hyperplasia. 11,12 It was reported by Weathers and Callihan in 1974 first time, 13 GCF is found predominantly in the first three decades of life with slight female predilection. The aetiology for GCF remains unknown and it seems that not be associated with chronic irritation.…”
Section: Casementioning
confidence: 93%
“…The aetiology for GCF remains unknown and it seems that not be associated with chronic irritation. 11,12 It typically manifests as an asymptomatic sessile or pedunculated mass in the anterior region of the jaw. [11][12][13][14] It is a nodule with the size of less than 1 cm, more frequently seen in the mandibular gingiva and the lesion might remain for several years.…”
Section: Casementioning
confidence: 99%